Mutation breeding of Phaseolus vulgaris L.: Studies on the effects of irradiation dosage to resolve a suitable procedure of handling M and M generations - Cheah, C. H.; Lim, E. S. (1982)
Seedling growth studies on gamma-irradiated seeds of Phaseolus vulgaris were conducted in the greenhouse and the field. No significant differences in germination scores between the unirradiated control and the seeds exposed to 10, 20, 25, 30, 35 and 40 Krads of gamma radiation were obtained. Exposure to 100 Krads, however, was lethal to the apical meristem. Growth of the epicotyl under greenhouse conditions was the most affected by gamma radiation. Based upon a 30% reduction in epicotyl length the optimum dose for irradiation was 30 Krads. At this level of irradiation the survival score at harvest under field conditions was 50% of that of the unirradiated control. Treatment with 30 Krads also gave the highest number of solid chlorophyll mutants.While not all the chlorophyll mutants were scored in the Bs (Sl gle seed bulk) populations, the % occurrence was consistently higher than that for the corresponding Bp (single pod bulk) populations. Based on these results, it is recommended that: a) the most suitable level of gamma radiation to use in a mutation breeding programme is 30 Krads; b) the M1 seeds should be field-planted at double the planting density of the control; c) the M1 plants should be harvested such that the Bs (single seed bulk) population be used for screening of the mutants.